1994
DOI: 10.1007/s002040050028
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the biochemical toxicology of uranyl nitrate in the rat

Abstract: High resolution 1H NMR spectroscopy of urine and plasma, conventional clinical chemical methods and histopathology have been applied to investigate the effects of uranyl nitrate (UN) on renal function and biochemistry in the Fischer 344 (F344) rat. Administration of UN (5-20 mg/kg) to male F344 rats resulted in a dose-related proximal nephropathy assessed conventionally by histopathology and urinary excretion of N-acetyl-beta-D-glucosaminidase (NAG), and related to changes in the patterns of low MW metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 23 publications
0
34
0
1
Order By: Relevance
“…The use of multivariate analysis of spectroscopic data has been pioneered by Nicholson and Lindon et al [9][10][11] for metabonomics analysis of biological fluids. In this approach, mathematical algorithms identify peaks/analytes that are responsible for group clustering, and have allowed many new and novel markers of drug toxicity to be identified.…”
mentioning
confidence: 99%
“…The use of multivariate analysis of spectroscopic data has been pioneered by Nicholson and Lindon et al [9][10][11] for metabonomics analysis of biological fluids. In this approach, mathematical algorithms identify peaks/analytes that are responsible for group clustering, and have allowed many new and novel markers of drug toxicity to be identified.…”
mentioning
confidence: 99%
“…Two papers (Bandara et al, 2003a,b) reported different subsets of results from the same experiment and were therefore treated as one paper for the purposes of this review. The objective of the study by Anthony et al (1994a), summarised in Table 1, was to provide a characterisation of the structural and functional consequences of uranyl nitrate nephrotoxicity using 1 H-NMR spectroscopy (without any subsequent bioinformatic data manipulation), blood and urine chemistry and histopathology. The NMR markers that did show changes generally correlated well with the changes detected by conventional clinical chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…Sustained leukopenia was induced by three intraperitoneal injections (150 mg/kg of body weight) of cyclophosphamide (Endoxan; Sarget Laboratories, Mérignac, France) per day starting 4 days before the bacterial challenge. Circulating leukocyte counts dropped from about 7,000/mm 3 initially to about 1,200/mm 3 on the day of infection, with neutrophil counts at about 100/mm 3 . The average leukocyte count reached 1,000/mm 3 of blood 1 day after infection and then increased progressively to 4,700/mm 3 of blood 3 days after infection (neutrophil count around 500/mm 3 ) to return to a normal count around 7,100/mm 3 of blood 5 days after infection (10,11).…”
Section: Methodsmentioning
confidence: 91%
“…Circulating leukocyte counts dropped from about 7,000/mm 3 initially to about 1,200/mm 3 on the day of infection, with neutrophil counts at about 100/mm 3 . The average leukocyte count reached 1,000/mm 3 of blood 1 day after infection and then increased progressively to 4,700/mm 3 of blood 3 days after infection (neutrophil count around 500/mm 3 ) to return to a normal count around 7,100/mm 3 of blood 5 days after infection (10,11). The organisms were introduced by intratracheal instillation as described in detail elsewhere (9).…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation